Incidence, Outcome and Determinants of Unplanned Extubation Among Pediatric Intensive Care Unit Addis Ababa, Ethiopia, 2023: Nested, Unmatched Case-Control Study Design - Mekonnen AS; Kebede Z; Demissie DB (Dove Medical Press, 2023)
Aster Shawel Mekonnen,1 Zegeye Kebede,2 Dereje Bayissa Demissie3 1Schools of Nursing, Yekatit 12 Medical College, Addis Ababa, Ethiopia; 2Schools of Nursing, St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia; 3Department of Neonatal, School of Nursing, St. Paul's Hospital Millennium Medical College, Addis Ababa, EthiopiaCorrespondence: Dereje Bayissa Demissie, Department of Neonatal Nursing, School of Nursing, St. Paul's Hospital Millennium, P.O. Box 1271, Addis Ababa, Ethiopia, Tel +251 912189560, Email derebayu@gmail.comBackground: Unplanned extubating is the most common adverse event occurring in intensive care units (ICUs) and significantly increases morbidity and mortality in children, but there is limited current evidence on unplanned extubating in Ethiopia. Therefore, this study aimed to determine the incidence, outcome, and determinants of unplanned extubating among children in the pediatric intensive care unit in Addis Ababa, Ethiopia, in 2023.Methods: A nested unmatched case-control design study was conducted at selected government hospitals in Addis Ababa from September 1, 2022, to April 30, 2023. A total of 198 intubated child patients (66 cases of unplanned extubating were nested with 132 controls of planned extubating) were followed up until they completed the full weaning process or based on hospital protocols. Data was collected through standardized data extraction, and the data was cleaned, entered into Epidata version 4.6, and exported to SPSS version 25.0 for further analysis. Binary and multiple logistic regression analyses were used to identify determinants of unplanned extubating, with an adjusted odds ratio (AOR) of 99% confidence interval (CI) at p value < 0.01.Results: The study revealed a high mortality rate of 15.65% among intubated children in pediatric intensive care units, and the incidence of unplanned extubating was 7.2 per 100 days. This study identified determinants of unplanned extubating among patients admitted to the pediatric intensive care unit: agitated patients (AOR = 3.708; 99% CI: 1.401- 9.81), working in night shift hours (AOR: 8.789; 99% CI: 2.37- 32.58), use of plaster or roll bandages separately (AOR = 4.12; 99% CI: 1.215- 13.96), A nurse-to-patient ration 1:2 (AOR: 6.65, 99% CI: 1.87- 23.69), intermittent sedation (AOR, 3.717; 99% CI, 1.017- 10.816), physically restrained (AOR = 3.717; 99% CI: 1.02- 13.54), and death outcome (AOR = 14.86, 99% CI: 3. 24- 68.097), respectively.Conclusion and Recommendations: This study found that the incidence and mortality rate of unplanned extubating were high, with identified determinants increasing the risk of unplanned extubating among patients admitted to pediatric intensive care unit. Therefore, policymakers and health planners should design further protocols and algorithms for the management of pediatric endotracheal intubation (ETT) quality of patient outcomes and to prevent unplanned extubating in a resource limited set up.Plain Language Summary: Unplanned extubating is a common adverse event in intensive care units that affects critically ill patients and increases morbidity and mortality rates. This study aimed to identify the determinants of unplanned extubating among children in Addis Ababa, Ethiopia, in 2023. This follow-up, unmatched case-control study included 198 intubated children, with 66 cases and 132 controls. The study used binary and multiple logistic regression analyses to identify determinants of unplanned extubating, and the Kaplan-Meier curve to determine survival outcomes. This study determined that the incidence of unplanned extubating was high, with identified determinants increasing the risk of unplanned extubating among patients admitted to pediatric intensive care units, such as agitation, night shift, intermittent sedation, endotracheal tube (ETT) taping by plaster or roll bandage separately, physical restraint, and the type of endotracheal tube (uncuffed). Therefore, policymakers and healthcare planners should consider these determinants during pediatric care unit training and guideline development for pediatric endotracheal intubation (ETT) mechanical ventilation outcomes.Keywords: unplanned extubation, incidence, outcome, pediatric intensive care unit and determinant